Peran Teknologi dalam Sistem Peringatan Dini Bencana Alam - Sari, Mumun Komala; Saepudin, Eli Apud; Lestari, Ninda Cyntia; Malindo, Melani; Agas, Agas (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
A disaster is an event or series of events that threatens and disrupts people's lives and livelihoods caused by natural and/or non-natural factors and human factors, resulting in human casualties, environmental damage, property losses, and psychological impacts. With its vast expanse of land and sea, Indonesia is not only rich in natural wonders, but also faces a variety of dire disaster threats. The government recorded more than 161 natural disasters, including earthquakes, volcanic eruptions, tsunamis, tornadoes, landslides and floods, between January and November 2014. This was not the case for the forest fires that ravaged almost all major islands in Indonesia. In dealing with this situation, it is important for all parties involved to work together, including the mass media. People's understanding of natural disaster warnings greatly influences their preparedness to deal with the impact of future disasters. The average percentage of households that are aware of signs or warnings of natural disasters in their neighbourhood, both in urban and rural areas, includes 11.35% and 8.08% respectively. The low level of community knowledge, especially regarding their own life safety, potentially increases the risk of becoming a victim when facing the impact of natural disasters.